2016
DOI: 10.1093/rheumatology/kev433
|View full text |Cite
|
Sign up to set email alerts
|

Fc-gamma receptor polymorphisms differentially influence susceptibility to systemic lupus erythematosus and lupus nephritis

Abstract: This study is the first to investigate the most relevant and functional single nucleotide polymorphisms and copy number variations of FcγRII and FcγRIII polymorphisms in one study population, enabling the determination of the individual contribution of each polymorphism in multivariable analysis. Three polymorphisms were shown to be independently associated with susceptibility to SLE. The novel findings of a negative association of the 2B.4 haplotype with LN, and increased expression of FcγRIIb on neutrophils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 41 publications
3
51
3
Order By: Relevance
“…In the present study, the FcγRIIa R131H and FcγRIIIb NA1/NA2 polymorphisms, which decrease the affinity of IgG binding and alter IC clearance [48], were not associated to either SLE susceptibility or lupus nephritis occurrence. The influence of these polymorphisms on both SLE susceptibility and outcome was diversely estimated.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…In the present study, the FcγRIIa R131H and FcγRIIIb NA1/NA2 polymorphisms, which decrease the affinity of IgG binding and alter IC clearance [48], were not associated to either SLE susceptibility or lupus nephritis occurrence. The influence of these polymorphisms on both SLE susceptibility and outcome was diversely estimated.…”
Section: Discussioncontrasting
confidence: 54%
“…However, in a study performed in a Brazilian population, Grecco et al [46] did not found any association between the FcγRIIIa F158V SNP and the SLE susceptibility. Besides, if the present study did not show any influence of the FcγRIIIa rs396991 SNP on SLE profile and outcome, the *G allele has been associated to lupus nephritis [45,47,48]. Indeed, the FcγRIIIa*V variant has a higher affinity towards IgG1 and IgG3, compared to the FcγRIIIa*F allele [44], which most likely results in a higher and more lasting activation of macrophages, via IC recognition.…”
Section: Discussionmentioning
confidence: 46%
“…For NK cell isolation we only used PBMCs from FCGR-genotyped donors that have two copies of FCGR3-158F and do not have a FCGR2C-ORF allele to exclude FcgRIIc as a confounding factor (33). Genotyping was performed as described before (34,35).…”
Section: Human Samplesmentioning
confidence: 99%
“…However, the higher concordance rate in monozygotic twins and increased risk of SLE in relatives highlight the genetic factors in SLE pathogenesis (Kuo et al, ). Various genes have been suggested as SLE predisposing factors which are commonly known as “ SLE susceptibility genes” such as human leucocyte antigen (HLA) (Armstrong et al, ), mannose‐binding lectin (MBL) (Tanha et al, ), Fc gamma receptor (FcγR) (Tsang‐A‐Sjoe et al, ) and programmed cell death‐1 (PD‐1) (Gianchecchi, Delfino, & Fierabracci, ). Moreover, the cytokine production by immune cells is aberrantly imbalanced in SLE which may be associated with exacerbated immune response and increased disease severity (Jacob & Stohl, ).…”
Section: Introductionmentioning
confidence: 99%